PENGARUH KEMUDAHAN PENGGUNAAN, KEPERCAYAAN DAN RESIKO TERHADAP MINAT MENGGUNAKAN METODE PEMBAYARAN SHOPEE PAYLATER PADA MAHASISWA AKUNTANSI - Zita Nelvina; Prima, Argo Putra (LPPM Universitas Putera Batam, 2025)
The motivations of accounting students in Batam to utilise Shopee Paylater are investigated in this research with respect to three factors: trust, simplicity of use, and risk. One payment method that has grown in popularity among young people, thanks to the emergence of fintech, is Shopee Paylater. Additional investigation on the elements impacting its attractiveness is necessary, however. The study collected quantitative data by having 150 accounting students from different Batam institutions fill out questionnaires. Using SPSS software, we performed multiple linear regression analyses on the collected data. Students' interest in utilising Shopee Paylater is favourably impacted by trust and convenience of use, and negatively by risk, according to the research. In a big way, these things determine what kids are interested in. Insights from this research may help fintech firms improve their services by boosting trust, making them easier to use, and reducing perceived risks. The significance of fostering financial awareness in the student body is further emphasised